Program Literasi Membaca Lima Halaman Satu Hari : Proses Menuju Membaca yang Lebih Baik di SDN 4 Megugede - M. Arif Syarif Hidayatullah; Muhamad Falak Cahyadi; Muhamad Alif Shidiq; nu Muhamad Al Furqoni; Miya Surasih Septianingrum (CV. ULIL ALBAB CORP, 2025)
Program